Laboratory manual : (McGraw - Hill, 2000)
This manual, designed to supplement "Hole's Essentials of Human Anatomy and Physiology" 7th edition, contains 47 laboratory exercises and reports, which integrate closely to the textbook. Exercises illustrate and review the anatomical and physiological facts and principles presented in the text and help students investigate some of these ideas in more detail.